Characterization of amine stabilized CdSe/ZnS core–shell quantum dots by using triarylpyrylium dyes. Issue 61 (13th June 2016) - Beltrán, Alicia; Burguete, M. Isabel; Luis, Santiago V.; Galindo, Francisco
Abstract : A new method to study the stabilizing primary amine ligands coordinated to the surface of CdSe/ZnS core–shell quantum dots has been developed. Abstract : A new method to study the stabilizing primary amine ligands coordinated to the surface of CdSe/ZnS core–shell quantum dots has been developed. The method is based on the reactivity of fluorescent 2, 4, 6-triarylpyrylium dyes with the aforementioned ligands to afford non-emissive 2, 4, 6-triarylpyridinium cations.